Percepción de la Eutanasia y factores asociados, en estudiantes de Medicina de la Facultad de Ciencias de la Salud de la Universidad Peruana de Ciencias Aplicadas en noviembre del año 2011 - García Hirsh, Samira Milagros Isabel (2014)
Background: Attitudes toward euthanasia among medical students have been studied in different countries except Peru. These attitudes are important in order to know if there is a correlation between what is taught, the law and other factors. Moreover, if associated factors with these perceptions are found we may be evidencing a trend of thought in which to act and from which changes can be generated. Objective: To assess attitudes toward euthanasia and to identify associated factors with these attitudes among medical students from first through fifth year from the School of Medicine of the Universidad Peruana de Ciencias Aplicadas. Materials and Methods: The present study analyses the attitudes toward euthanasia in medical students of Lima, Peru. A crosssectional study was performed and the entire population was included. The questionary was previously validated with a pilot study and statistical test (Cronbach's alpha 0.84). The association between categorical variables was tested using the chi square test (p<0.05). A Poisson regression model with robust variance estimation was used to compute Prevalence Ratios as indicators of the strength of association between the predictor variables and being in favor of euthanasia (CI 95%). Results: A total of 551 medical students received an anonymous questionnaire; 550 completed it. From these, 343 (62.4%) were women and the median age of the subjects was 19. Most of the students were Catholics (80%) and the majority of subjects came from first (30.5%) and second year (30.7%) of study. The number of students who had a positive attitude toward euthanasia was 331 (60%). The male gender (RR 1.31 CI 1.15 – 1.49) and Agnosticism (RR 1.35 CI 1.16 – 1.57) showed to be related to a positive attitude toward euthanasia compared with female gender and Catholicism respectively. Years of medical training, year of study and health bioethics education were analyzed; however no association was found. Other results showed that of 286 students who would not practice euthanasia 28.3% had a positive attitude towards it, while from 264 who would practice it 5.3% had a negative attitude. Conclusion: A high proportion of the population had a proeuthanasia attitude. Male gender and agnosticism were the only associated factors with a positive attitude. These results give enough reason to focus on case-based teaching and also to enhance medical bioethics education on palliative medicine. The findings could be due to a change in the attitudes of young people towards greater freedom and individual judgment in the context of a more liberal environment. These findings are comparable with those found in other studies in Latin America. It is important to highlight the importance of the current legal framework and how it could affect the attitudes toward euthanasia in medical students; however, in this investigation such association was not found. The educational model taught to students in regard to bioethics is essential for decision-making in the management of a patient, which should be based on bioethical principles, code of ethics, moral and the current legal framework.